помогите решить уравнения.

х+12=3х

-7-х=3х+17

3(х-3)=х+2(х+5)

-4(х+2)+3(х-1)-2=4(х-2)+9

2

Ответы и объяснения

2012-12-18T13:51:49+04:00

х+12=3х

2х=12

х=6

остальные незнаю если не сложно скажи спасибо

Лучший Ответ!
2012-12-18T14:06:42+04:00

х+12=3х       -7-х=3х+17                 3(х-3)=х+2(х+5)          -4(х+2)+3(х-1)-2=4(х-2)+9

х-3х=-12        -х-3х=17+7                 3х-9=х+2х+10              -4х-8+3х-3-2=4х-8+9

-2х=-12          -4х=24                        3х-х-2х=10+9                -4х+3х-4х=-8+9+8+3+2

2х=12              х=24/(-4)                    х=19                               -5х=14 |:(-5)

х=12/2             х=-6                                                                     х=14/5

х=6                                                                                                 х=2 , 4/5